2021
DOI: 10.1186/s40580-021-00254-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production from water electrolysis: role of catalysts

Abstract: As a promising substitute for fossil fuels, hydrogen has emerged as a clean and renewable energy. A key challenge is the efficient production of hydrogen to meet the commercial-scale demand of hydrogen. Water splitting electrolysis is a promising pathway to achieve the efficient hydrogen production in terms of energy conversion and storage in which catalysis or electrocatalysis plays a critical role. The development of active, stable, and low-cost catalysts or electrocatalysts is an essential prerequisite for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
403
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 766 publications
(472 citation statements)
references
References 77 publications
4
403
0
Order By: Relevance
“…The only truly "green" way to make H 2 is by water splitting, with the energy required generated by renewables or nuclear power. There are demonstration systems that use the reaction between a high temperature metal salt and water [30], but the most obvious way to generate H 2 is by electrolysis of water [31]. Unfortunately, current electrolysers are not very efficient [32].…”
Section: Hydrogenmentioning
confidence: 99%
“…The only truly "green" way to make H 2 is by water splitting, with the energy required generated by renewables or nuclear power. There are demonstration systems that use the reaction between a high temperature metal salt and water [30], but the most obvious way to generate H 2 is by electrolysis of water [31]. Unfortunately, current electrolysers are not very efficient [32].…”
Section: Hydrogenmentioning
confidence: 99%
“…Furthermore, because of the formation of carbon-free products, there is a significant lowering of greenhouse gas production in contrast to the traditional methods ( Ashok et al, 2008a ). It has also been reported that hydrogen production through this method reduces CO x emission by about 27% and can also reduce the global climatic effects ( Weger et al, 2017 ; Wang et al, 2021a ). The decomposition of methane requires a large amount of energy, almost equivalent to its formation.…”
Section: Introductionmentioning
confidence: 99%
“…Even pathways like hydrogen production via splitting of water using electricity have gained a widespread attraction among the scientific community ( Figure 2 ) ( Wang et al, 2021a ). Renewable resources or non-renewable resources are used as feedstock during the electricity driven water splitting ( Rozzi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations